Development and validation of questionnaire to assess perceptions and attitudes towards intimate partner violence among premarital young adults in Kelantan - Hanafi, Wan Soliha Wan Mohd (2022)
Conclusion: The MY-PAIPVQ is valid and reliable to assess perceptions and attitudes towards IPV among premarital young adults. Good perceptions and attitudes towards IPV by young adults may enable and empower them to recognize abusive behavior is taking place and how to take appropriate action against it. Prevention and intervention efforts could be improved using language that young adults find relevant.